2014
DOI: 10.1167/iovs.14-14818
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Thrombin in Proliferative Vitreoretinopathy

Abstract: Thrombin activity is increased in vitreous of patients with established PVR and is involved in the activation of proinflammatory and profibrotic pathways in RPE cells. Inhibition of thrombin activity may therefore represent a potential treatment option for proliferative vitreoretinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 32 publications
1
47
2
Order By: Relevance
“…1, 2) [1]. In contrast to our previous experiment, which showed significantly higher thrombin activity in established PVR, we could not detect a difference in F1+2 and TAT values between patients with uncomplicated RRD and patients with established PVR.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…1, 2) [1]. In contrast to our previous experiment, which showed significantly higher thrombin activity in established PVR, we could not detect a difference in F1+2 and TAT values between patients with uncomplicated RRD and patients with established PVR.…”
Section: Discussioncontrasting
confidence: 99%
“…In the previous experiments, we used the small thrombin-specific chromogenic substrate Tos-Gly-Pro-Arg-pNA (MW 662.7 Da) for the measurements of intravitreal thrombin activity [1]. Although the substrate is very well split by thrombin, other serine proteases such as plasma kallikrein and plasmin are also known to act on the substrate due to its small MW.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under these conditions, Müller glia and retinal astrocytes release factors such as vascular endothelial growth factor (VEGF) and cytokines that contribute to further disrupt the BRB 6 and to promote MC proliferation. 7 Recent studies have shown that thrombin activity is increased in the vitreous from proliferative vitreoretinopathy (PVR) patients, 8 suggesting thrombin involvement in the pathogenesis of PVR, characterized by the proliferation, dedifferentiation, and migration of MCs and transdifferentiation of RPE cells into the vitreous and the assembly of contractile cellular membranes on retinal surfaces, thus promoting retinal detachment. 9 It has been previously shown that thrombin stimulates glial cell proliferation in a dosedependent manner 10,11 and that it has an inhibitory effect on inwardly rectifying K þ current (IK(IR)).…”
Section: M¨umentioning
confidence: 99%